Grounding Zone of Helheim Glacier, Greenland, From Terrestrial Radar Interferometry - Jae Hun Kim; Eric Rignot; Hanning Chen; David Holland; Denise Holland (Geophysical Research Letters)
Abstract Helheim Glacier, in East Greenland, is a major outlet glacier that discharges about 33 Gigatons of ice per year into the ocean. Helheim has been undergoing a retreat since 2003. Using a portable terrestrial radar interferometer that scans the glacier every 2 min, we characterize its regime of tidal flexure at the ice front margin in relation to oceanic tide, bed slope, and iceberg calving events. The data reveals the presence of a central bed ridge that acts as a fulcrum, with one side of the glacier moving in phase with the tide, while the other is moving out of phase with a reduced amplitude. We detect seawater intrusions of one full thickness beneath the glacier front at high tide. Following tabular calving events, most ice flexing ceases, indicating that the ice front becomes grounded and that calving events involve ice blocks that are already afloat.